The Influence of Macroeconomic Indicators and Bank Internal Factors on Credit Risk in Developing Countries - Henny Setyo Lestari; Bahtiar Usman; Wafi Suryo Laksono; M. Hussin Abdullah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the determinants of credit risk in commercial banks in Indonesia as measured by Non-Performing Loans (NPL), as the main indicator of banking system stability. This study uses a quantitative method with a panel data regression approach to evaluate the influence of various factors on credit risk. Data were obtained from financial statements and annual reports of banks listed on the Indonesia Stock Exchange. The sample consisted of 36 banks during the period 2019–2023, resulting in 180 observations. The analysis was conducted using multiple linear regression with fixed and random effect models through EViews software. The results of the analysis show that variables such as interest rates, bank size, return on assets (ROA), loan loss provisions (LLP), capital adequacy ratio (CAR), and asset quality have a significant effect on NPL. In contrast, gross domestic product (GDP) and inflation do not show a significant effect. These findings indicate that interest rates and ROA are significant new contributors to NPL fluctuations in the Indonesian banking sector during the study period.